The arrival of AI to the cities: platform urbanism and new regimes of governmentality - José Luis Blasco Ejarque; Francisco Javier Tirado (Revista CIDOB d'Afers Internacionals)
This paper analyses “platform urbanism” as a post-biopolitical dispositive of domination and subjectivation characteristic of the “performance societies” of the 21st century. It examines how algorithmic platforms expose citizens to new control and power relations through techno-social dispositives such as artificial intelligence (AI). The authors close with the idea that the rollout of platform urbanism is a model of “algorithmic governmentality” that fosters the advent of new practices of dissent based on “open innovation”.